2021
DOI: 10.1109/access.2021.3069793
|View full text |Cite
|
Sign up to set email alerts
|

Time Difference of Arrival Based Indoor Positioning System Using Visible Light Communication

Abstract: Visible Light Communication (VLC) is a novel optical wireless communication technology which uses Light Emitting Diodes (LEDs) and Photodiodes for coherent detection and very-high-data rate data communication system. The stringent Line of Sight (LoS) requirement in VLC makes it very suitable for Indoor Positioning System (IPS), to be used for autonomous and smart city infrastructure. The current work aims to implement a real time IPS system using VLC link in Network Simulator (NS-3). The VLC module is implemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…Moreover, AoA requires complex hardware with proper calibration and synchronization for precise position estimation. The ToA method depends on the propagation time duration of the packet from the anchor node to the target node [ 17 ]. ToA-based indoor localization is less complex than the AoA method but is dependent on synchronization of the source and the destination node.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, AoA requires complex hardware with proper calibration and synchronization for precise position estimation. The ToA method depends on the propagation time duration of the packet from the anchor node to the target node [ 17 ]. ToA-based indoor localization is less complex than the AoA method but is dependent on synchronization of the source and the destination node.…”
Section: Introductionmentioning
confidence: 99%
“…Distance and trilateration are determined using the TDOA method, and they concluded that TDOA method is more reliable than other methods like AOA. Naz et al [18] proposed a technique called Visible Light Communication (VLC) to determine an object's position with minimum localization error, while a signal flows via an optical channel. Uradzinski et al [19] The balanced K-nearest neighbors method and the Bayesian algorithm have been developed for a novel data filtering solution with an average accuracy of 0.81m or less.…”
Section: Literature Surveymentioning
confidence: 99%
“…When it comes to findving the x-coordinate, the equation 17 expressed as (17) Suppose when we have to determine the equation of line of best fit for the given data, the equation of least square line is given by y = a + bx, where the equations ( 18) for a is and for b it is ……. (18) In order to calculate the covariances, sensors need to exchange their current position predictions with those of their neighbors and the distance between them. The sensor that will receive several estimates can be positioned for better combination among that low distance will be considered.…”
Section: K= ( ) (5)mentioning
confidence: 99%
“…Piccinni et al [17] demonstrated that accuracy of under 2 cm can be achieved using the Time Difference Of Arrival (TDOA) positioning technique coupled with Orthogonal Frequency Division Modulation (OFDM). A few-centimeter accuracy can also be achieved with VLC technology [18,19] on account of the more expensive hardware and computational setups. However, as a drawback of VLC technology, constant line-of-sight (LOS) is necessary for correct operation, coupled with the demand that light sources must stay on all the time [20].…”
Section: Introductionmentioning
confidence: 99%